2010
DOI: 10.5210/bsi.v19i0.3080
|View full text |Cite
|
Sign up to set email alerts
|

Delay Discounting of Different Commodities Varies as a Function of Political Party Affiliation in a College Sample

Abstract: Delay discounting has been used as a measure of both self control and of value for a particular commodity. Two hundred sixty five college psychology students who self identified as being either a Democrat or a Republican completed a delaydiscounting task involving five different commodities (two monetary values, retirement income, Federal legislation, and medical treatment). Analyzing the area under the discounting curve, results showed that Democrats discounted all commodities to a greater extent than did Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…As noted above, previous research (Weatherly, 2010) has demonstrated differences in levels of discounting as a function of political party affiliation. In that study, however, Democrats displayed significantly more discounting than Republicans.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…As noted above, previous research (Weatherly, 2010) has demonstrated differences in levels of discounting as a function of political party affiliation. In that study, however, Democrats displayed significantly more discounting than Republicans.…”
Section: Discussionmentioning
confidence: 64%
“…Phrased differently, they should be more likely than those with conservative ideologies to support legislation that delivers delayed benefits to society. One the other hand, Weatherly (2010) reported finding that university students who self-identified as Democrats displayed significantly more, rather than less, discounting of four different outcomes than did self-identified Republicans. Likewise, research has demonstrated that discounting of different outcomes sometimes varies as a function of aspects of the participants' religiousness (Weatherly & Plumm, in press;Weatherly & Terrell, 2011).…”
mentioning
confidence: 99%
“…On the one hand, previous research has found that individuals with self-reported liberal ideologies demonstrate shallower discounting for delayed outcomes (Hardisty et al, 2010 ; Rattner, Yagil, & Shermn-Segal, 2003 ). On the other hand, Weatherly ( 2010 ) reported that individuals with self-reported liberal ideologies demonstrated steeper discounting. In light of the current study’s findings and the unreliable findings in previous research, future studies should investigate the conditions under which political affiliation affects measures of delay discounting.…”
Section: Discussionmentioning
confidence: 99%